Prevalence of Non-Fistulous Urinary Incontinence among Nonparturient Women in A Tertiary Hospital - Olukemi Bello, Oluwasomidoyin (Journal of Women's Reproductive Health, 2018)
Objective: To determine the prevalence and risk factors of non-fistulous urinary incontinence (UI) among non-parturient women at University College Hospital, Ibadan, Nigeria. Methods: A hospital based cross sectional study of 500 non-parturient women presenting with non- fistulous gynaecological symptoms at the University College Hospital, Ibadan. An interviewer administered questionnaire was used to obtain information. Data were analyzed using SPSS version 20. Data analysis involved descriptive statistics, bivariate and multivariate analysis to determine the risk factors of urinary incontinence. Results: Mean age was 36.61 (SD=10.1) years and almost all (83.2%) were married. Prevalence of urinary incontinence is 21.4%. Majority (40.6%) had symptoms of stress urinary incontinence and 8.0% had urge urinary incontinence. Only 19.6% of those who leaked urine in the last one month sought medical attention despite visiting the hospital for other ailment(s), while of those that had ever leaked urine, 13.1% of them ever sought medical attention. Risk factors for UI were age at first delivery (OR=21.21, 95%CI=2.179-206.478), marital status (OR=0.142, 95%CI=0.044-0.454), chronic illness (OR=3.987, 95%CI=2.147-7.405) and history of prolonged labour (OR=3.111, 95%CI=1.584-6.110). Conclusion: UI is not uncommon in Nigeria. The identified predisposing factors were low age at first delivery, history of prolonged labour and chronic illness. There is need to sensitize women of the symptoms and complications associated with urinary incontinence as well as its prevention and need to seek medical care if they have the symptoms.
Keywords: prevalence; urinary incontinence; non-parturients